Differences and Similarities in the Clinicopathological Features of Pancreatic Neuroendocrine Tumors in China and the United States: A Multicenter Study. Issue 7 (February 2016) - Zhu, Li-Ming; Tang, Laura; Qiao, Xin-Wei; Wolin, Edward; Nissen, Nicholas N.; Dhall, Deepti; Chen, Jie; Shen, Lin; Chi, Yihebali; Yuan, Yao-Zong; Ben, Qi-Wen; Lv, Bin; et al.
Abstract : Abstract: The presentation, pathology, and prognosis of pancreatic neuroendocrine tumors (PNETs) in Asian patients have not been studied in large cohorts. We hypothesized that the clinicopathological features of PNETs of Chinese patients might be different from those of US patients. The objectives of this study were to address whether PNETs in Chinese patients exhibit unique clinicopathological features and natural history, and can be graded and staged using the WHO/ENETS criteria. This is a retrospective review of medical records of patients with PNETs in multiple academic medical centers in China (7) and the United States (2). Tumor grading and staging were based on WHO/ENETS criteria. The clinicopathological features of PNETs of Chinese and US patients were compared. Univariate and multivariate analyses were performed to find associations between survival and patient demographics, tumor grade and stage, and other clinicopathological characteristics. A total of 977 (527 Chinese and 450 US) patients with PNETs were studied. In general, Chinese patients were younger than US patients (median age 46 vs 56 years). In Chinese patients, insulinomas were the most common (52.2%), followed by nonfunctional tumors (39.7%), whereas the order was reversed in US patients. Tumor grade distribution was similar in the 2 countries (G1: 57.5% vs 55.0%; G2: 38.5% vs 41.3%; and G3: 4.0% vs 3.7%). However, age, primary tumor size, primary tumor location, grade, and stage of subtypes of PNETs were significantly different between the 2 countries. The Chinese nonfunctional tumors were significantly larger than US ones (median size 4 vs 3 cm) and more frequently located in the head/neck region (54.9% vs 34.8%). The Chinese and US insulinomas were similar in size (median 1.5 cm) but the Chinese insulinomas relatively more frequently located in the head/neck region (48.3% vs 26.1%). Higher grade, advanced stage, metastasis, and larger primary tumor size were significantly associated with unfavorable survival in both countries. Several clinicopathological differences are found between Chinese and US PNETs but the PNETs of both countries follow a similar natural history. The WHO tumor grading and ENETS staging criteria are applicable to both Chinese and US patients. Abstract : Supplemental Digital Content is available in the text